THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Vira Elmia Putri; Irwin Sukrisno Sugeng; Andri Rizko Yulianto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This research aims to determine the effect of the work environment and work motivation on employee performance in the finance division of RSUD Koja North Jakarta. This research method uses quantitative statistical methods. The population in this study is the employees of the finance division of RSUD Koja North Jakarta, and the research sample consists of 40 people. Data analysis uses multiple linear regression tests with the assistance of SPSS 25 software. The results of this study are (1) The work environment has a positive and significant effect on employee performance based on the T-test results because the Sig value of 0.849 > 0.05 and the calculated t value of 191 > the table t value of 2.026, thus Ho1 is rejected and Ha1 is accepted. (2) Work motivation has a positive and significant effect on employee performance based on the T-test results because the Sig value of 0.008 < 0.05 and the calculated t value of 2.818 > the table t value of 2.026, thus Ho2 is rejected and Ha2 is accepted. (3) The work environment and work motivation together have a positive and significant effect on employee performance.